HUBUNGAN PELATIHAN HANTARAN PENGANTIN DENGAN MOTIVASI BERWIRAUSAHA WARGA BELAJAR DI PKBM INSAN MULIA DESA KEDAWONG KEC. DIWEK KAB. JOMBANG - Muhammad Rois Amrulloh; Indrawati Theresia (JPUS: Jurnal Pendidikan Untuk Semua, 2020)
Bridal delivery is a gift or offering given by the family of the bridegroom to the bride and groom as a form of respect, or it can also be said that the bridal delivery or peningset (Javanese) is a sign of bonding. Entrepreneurial motivation is a major aspect for citizens learning through training education. This entrepreneurship motivation is a strong motivation for someone to become an entrepreneur. The purpose of this study was to determine the correlation between bride delivery training and entrepreneurial motivation of citizens to study at PKBM Insan Mulia. This research method uses a quantitative approach to the type of correlational research. The number of respondents in this study were 30 residents who learned bridging delivery. Data collection techniques used were questionnaire, observation and documentation. Data analysis techniques using the product moment formula to analyze the results of the questionnaire.The results showed that the r count is greater than r table (0.686â‰¥0.361) which means there is a positive correlation between bride delivery training with entrepreneurship motivation, Proven Ha is accepted and Ho is Rejected. The relationship between the two variables is included in the category of interval 0.60 - 0.799. Significant test results show that the price of t count is greater than t table (6.855â‰¥2.048) meaning that there is a positive and significant relationship between bride delivery training programs and entrepreneurial motivation.